UPAYA MASYARAKAT ADAT SENDI DALAM PEMBENTUKAN DESA ADAT MENURUT UNDANG UNDANG NO 6 TAHUN 2014 TENTANG DESA PERSPEKTIF AL-MAWARDI - Satrio Budiharto (Program Studi Hukum Tata Negara Fakultas Syariah UIN Maulana Malik Ibrahim Malang, 2019)
Previously, Sendi was a village complete with government officials in 1912. This area was reported in the mass media as disappearing from the map ofMojokerto district, East Java in 1989. Permendagri No.56 of 2015 concerning Code and Data of the Government Administration Area, Sendi village was notlisted in the Mojokerto Regency Administration area, also not included in 299 villages and 5 kelurahan in Mojokerto Regency. In this case the state regulates theLaw on Villages in accordance with Law Number 6 of 2014 concerning Villages. As for the obstacles faced by the Ex-Sendi Society on the implementation of theformation of traditional villages that exist in the Act, causing problems to be analyzed. The formulation of the problem compiled is what are the efforts of thecommunity in forming the Customary Villages according to Law No. 6 of 2014, as well as the obstacles they experienced, and the role of the government in the AlMawardi Perspective. This study uses a type of Empirical Juridical research with Sociological-Juridical approach that produces descriptive data. This research wasconducted in Pacet, Mojokerto Regency. In collecting data, interviews were conducted with observations and documentation to a number of informants whohad been determined. Data processing is done by Re-examination (Editing), Classification (classifying), Verification (verifying), Analysis (Analizing). Theresults obtained explain that the Ex-Joint Community has tried to form a People's Struggle Forum (FPR), also gave letters, and conducted dialogues with relatedinstitutions of the Village and Regency Governments, as well as the Provinces to try to form a Customary Village, but were rejected and could not get recommendations.